2012
DOI: 10.14746/ssllt.2012.2.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic nature of motivation in language learning: A classroom perspective

Abstract: When we examine the empirical investigations of motivation in second and foreign language learning, even those drawing upon the latest theoretical paradigms, such as the L2 motivational self system (Dörnyei, 2009), it becomes clear that many of them still fail to take account of its dynamic character and temporal variation. This may be surprising in view of the fact that the need to adopt such a process-oriented approach has been emphasized by a number of theorists and researchers (e.g., Dörnyei, 2000Dörnyei, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 36 publications
1
52
0
5
Order By: Relevance
“…To get the view of changes over time, longitudinal designs are essential (e.g., Ortega & Iberri-Shea, 2005;Pawlak, 2012). Then, of course, a richly contextual ethnography is especially useful in studying complex systems, where it is assumed that the observer is part of the system being observed.…”
Section: Research Methods For Studying Complex Systemsmentioning
confidence: 99%
“…To get the view of changes over time, longitudinal designs are essential (e.g., Ortega & Iberri-Shea, 2005;Pawlak, 2012). Then, of course, a richly contextual ethnography is especially useful in studying complex systems, where it is assumed that the observer is part of the system being observed.…”
Section: Research Methods For Studying Complex Systemsmentioning
confidence: 99%
“…The tool is straightforward and intuitive and, most importantly, can be used in the context of the classroom without disturbing the natural progression of the lesson. It is similar to Pawlak's () “motivational grid” (p. 257), which measured motivation with time intervals of five minutes on a 1–7 scale.…”
Section: Methodsmentioning
confidence: 99%
“…Hotho () for example found that even when a learner's overall L2 motivational profile remained relatively stable during a semester, short term motivation was susceptible to considerable change: “[T]he teachers may sense changes or fluctuations from week to week, as a result, perhaps, of a piece of homework, a test, or a class that was particularly inspiring or noninspiring” (p. 326). Similarly, Pawlak () and Poupore () traced the development of groups of learners for the duration of several classroom hours, and they, too, highlighted the dynamic nature of short‐term motivation. Other investigations have documented long‐term tendencies in motivational evolution, usually evidencing some decline in levels of motivation during the course of extensive institutional engagement (e.g., Chambers, ; Dörnyei, Csizér, & Németh, ; Gardner et al, ).…”
Section: Motivational Dynamicsmentioning
confidence: 99%
“…Therefore, the study suggested the existence of cross-cultural differences in L2 selves and successfully validated the L2 Motivational Self System in Asian cultural contexts. Pawlak (2012) investigated the fluctuations in motivation in an L2 English class with 28 Polish senior school students over a period of four weeks. He collected data through questionnaires, observations and interviews.…”
Section: The L2 Motivational Self Systemmentioning
confidence: 99%